Representasi Feminisme dalam Film Lady Bird - Aryawan, Dewi Nandini; Sugiarica Joni, I Dewa Ayu; Alit Suryawati, I Gusti Agung (E-Jurnal Medium; Vol 1 No 2 (2021): Jurnal Ilmu Komunikasi 2021, 2021)
Film as a form of mass communication have the ability to influence society. The influence of film on society is used by filmmakers in providing messages in the form of views on social phenomena such as patriarchal culture. Filmmakers use a view of feminism as a resistance to patriarchal culture in their works. One of the films that uses feminist views to fight patriarchy is Lady Bird. This paper describes the signs of feminism in film using Peirce's semiotic analysis. Signs of feminism are depicted in verbal and nonverbal film scenes in the form of dialogues and actors' performances throughout the film. The view of feminism in the Lady Bird implies the resistance of patriarchal culture through the mass media for people's views. Keywords: Lady Bird, Film, Semiotic, Feminism.